Complications of Regional Anesthesia : Principles of Safe Practice in Local and Regional Anesthesia - Finucane, Brendan T.; Tsui, Ban C.H (Springer International Publishing : Imprint: Springer, 2017)
Reflecting the rapid growth of pain medicine and of ultrasound as a tool, this Third Edition is more comprehensive and inclusive than previous editions and features additional pages, tables, diagrams, and color illustrations. In addition to the discipline of Anesthesiology, other specialists, who use local and regional anesthesia techniques, (surgeons, ophthalmologists, emergency medicine physicians and dentists), have also contributed to this edition of the book. Complications of Regional Anesthesia, with its newly added subtitle, Principles of Safe Practice in Local and Regional Anesthesia, stresses the relatively new emphasis and importance on safety and prevention and broadens the discussion to include the practice and administration of not just regional but also local anesthesia. Each chapter has been thoroughly revised, brought up-to-date, and features full color images. Individual chapters cover complications associated with specific nerve blocks; IV and catheter methods; obstetric regional anesthesia; pediatric regional anesthesia; ophthalmic regional anesthesia; and treatment of acute and chronic pain.
Keywords: Medicine.; Anesthesiology.; Pain medicine.; elektronické knihy; electronic books